Deep thermal regime, temperature induced over-pressured zone and implications for hydrocarbon potential in the Ankleshwar oil field, Cambay basin, India. (1st August 2018) - Ganguli, Shib Sankar; Vedanti, Nimisha; Pandey, O.P.; Dimri, V.P.
Graphical abstract: Highlights: Moderate overpressured zone beneath the Ankleshwar oil field is linked to the high temperature anomaly. The southern part of the Cambay basin is anomalously warm and not very different from its northern part. Classic signatures of fluid expansion and consequent gas generation in a shale bearing strata are observed. Low conductive shales of this basin are potential target for shale gas exploration. Abstract: Ankleshwar oil field situated in the southern part of the Cambay basin, forms one of the prominent onshore Tertiary hydrocarbons bearing regions of western India. A detailed multiparametric lithological analysis of the well logs obtained from 16 deep wells, indicate conspicuous trend of inversion in density and transit time below a depth of about 1250 m, which coincides with the presence of moderately high overpressure zone within the reservoir and appear temperature induced. Estimated temperature gradient based on the corrected Bottom Hole Temperatures, recorded at different depths in the boreholes, are found to be quite high (∼53 °C/km) at deeper levels, especially in the overpressured zone, that contains low conductive Cambay shales. Estimated heat flow of 75.2 mW/m 2 at Ankleshwar, together with high Moho temperatures of about 880 °C and an extremely shallow depth to subcrustal melting (∼50 km), would suggest that not only the northern part, the entire hydrocarbon bearing Cambay basin, along with the Mumbai offshore region, is anomalously warm. In view of the presence of high thermal anomaly, low conductive shales of the Cambay basin might be a good target for shale gas investigation, as the prevailing in situ temperature is one of the crucial factors in oil-to-gas cracking.